Influence of Different Vehicles on the pH and Surface Tension of Calcium Hydroxide Pastes - Erbay Türkaydın, Dilek; Tarçın, Bilge; İriboz, Emre; Kaplan Tuna; Gökmen, Emel; Sazak Öveçoğlu, Hesna; Garip Berker, Yıldız (My University, 2013)
The aim of this study was in vitro evaluation and comparison of pH levels and surface tension of calcium hydroxide [Ca(OH)2 ] paste prepared with different vehicles such as distilled water, citanest, glycerin, and procaine. Forty extracted human maxillary incisors were used for pH analysis in the study. Teeth were randomly divided into 4 groups as follows: Group I: Ca(OH)2 and distilled water paste; Group II: Ca(OH)2 and glycerin paste; Group III: Ca(OH)2 and citanest paste and Group IV: Ca(OH)2 and procaine paste. In all groups, pH measurements were performed at the 15th, 30th and 45th minutes; 2nd, 24th and 48th hours, and 7th and 14th days. The powder of Ca(OH)2 and liquids were mixed to the weight ratio 3:2 (3 ml liquid and 2 g powder) for the surface tension measurements. The surface tension of Ca(OH)2 mixtures was measured using a tensiometer device. All measurements were repeated five times for each sample and by arithmetic means were calculated. The data were recorded and statistical analysis was performed with a significance level set at p<0.05. The combination of Ca(OH)2 with procaine resulted in significantly higher pH values compared to the other pastes. Distilled water mixed with Ca(OH)2 represented the highest surface tension values (77,5 dynes/cm). The mixture of procaine or citanest with Ca(OH)2 powder presented the lowest surface tension values of all the groups (61,6 and 56,1 respectively). Considering the pH values obtained in this study, procaine might be used as a vehicle for Ca(OH)2 powder. Citanest, with the lowest surface tension values, seems to be the most favorable vehicle for Ca(OH)2 .
Keywords: Calcium hydroxide, citanest, pH, procaine, surface tension